2020
DOI: 10.1007/s12282-020-01117-9
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional objective aesthetic evaluation to replace panel assessment after breast-conserving treatment

Abstract: Background Two-thirds of patients with early breast cancer undergo breast-conserving treatment (BCT). Aesthetic outcome is important and has long term implications for psychosocial wellbeing. The aesthetic goal of BCT is symmetry for which there is no gold-standard measure. Panel scoring is the most widely adopted assessment but has well-described limitations. This paper describes a model to objectively report aesthetic outcome using measures derived from 3-dimensional surface images (3D-SI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This is important, because over 40% of women undergoing mastectomy and reconstruction perceived their outcome to be worse than expected—particularly with regards to aesthetics [ 11 ]. Surgical teams already derive added value from utilising 3D images for aesthetic assessment after breast surgery [ 12 ]. Furthermore, an early phase randomised-controlled-trial suggested that viewing 3D images improved patient confidence going into surgery when compared with 2D photographs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because over 40% of women undergoing mastectomy and reconstruction perceived their outcome to be worse than expected—particularly with regards to aesthetics [ 11 ]. Surgical teams already derive added value from utilising 3D images for aesthetic assessment after breast surgery [ 12 ]. Furthermore, an early phase randomised-controlled-trial suggested that viewing 3D images improved patient confidence going into surgery when compared with 2D photographs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetic outcome after breast reconstructive surgery has been found to affect the patients' quality of life and psychosomatic wellbeing [14]. As modern treatments have ensured excellent survival rates of breast cancer patients, the aesthetic outcome of the surgical procedure demands more attention in addition to disease control [28]. Subjective evaluation based on a visual assessment by one or more observers, including radiation oncologists and plastic surgeons, are employed frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel visual breast assessment method uses an optical flow algorithm in MATLAB which objectively classifies and numerically scores breast asymmetry [27]. Considering all the statistical data, 3D objective assessment has been proven to be more consistent and accurate, leading it to be a prospective replacement of subjective panel assessment in terms of aesthetic evaluation after breast conserving treatment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Breast volume is a crucial factor and a key metric that defines breast symmetry, influencing cosmesis and patient satisfaction after breast surgery [ 1 , 2 , 3 ]. Several objective methods for evaluating breast volume and symmetry are widely used, and these methods are based on linear distances such as anthropometric measurements [ 4 , 5 , 6 , 7 ], volumetric measurements using medical imaging technology [ 8 , 9 , 10 , 11 ], techniques like water displacement [ 12 , 13 , 14 , 15 , 16 ], and casting techniques [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%